Successful Endoscopic Removal of 42 Magnetic Balls - Dole, Michael; Hiremath, Girish (Journal of Digestive Endoscopy, 2017)
Foreign body ingestion in pediatric patients is a common emergency department presentation. Despite a ban and recall in 2014 for the magnetic toy “Buckyballs” due to posing a deadly risk if ingested, clinical cases continue to occur. The need for surgical management in the setting of multiple magnet ingestions is related to compromised blood supply when at least two magnets are attracted while separated by gastrointestinal mucosa, and previous studies have indicated that the majority of multiple magnet ingestions require surgical intervention. In the setting of a known recent ingestion, endoscopic removal can potentially safely avoid the morbidity and mortality associated with surgical procedures. We present an interesting clinical case of multiple magnetic ingestion managed with endoscopic procedure.
Keywords: Buckyballs; endoscopy; foreign body; fullerenes; magnet